2022
DOI: 10.3365/kjmm.2022.60.4.282
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Vacuum Centrifugal Casted Ti-6Al-4V Alloy by Casting and Heat Treatment

Abstract: The Ti-6Al-4V alloy has been widely used for structural materials due to high specific strength property, however it is difficult to cast because of high reactivity at high temperature. In this study casting characteristics and post-casting heat treatment were studied in the cast Ti alloy. The cast alloy was prepared using high-frequency induction heating and horizontal vacuum centrifugal casting to reduce reaction with crucible and mold by minimizing overheating of the molten metal and casting fast. In the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A lot of research has been conducted on cast Ti-6Al-4V. Feng et al [12], Zhu et al [13], Lee et al [14], and Wen et al [15] have determined the mechanical properties of Ti-6Al-4V cast alloys and the mechanical properties of Ti-6Al-4V casting alloys in terms of the machining conditions, the addition of Ti-TiB2 nanoparticles, vacuum centrifugation, Ni sandwich method from a single point of view, and the mechanical properties of Ti-6Al-4V casting alloys and the mechanical properties of Ti-6Al-4V casting alloys from a single point of view, in addition to 4V casting alloy's mechanical properties as well as strength. In addition, some scholars have also investigated the properties of Ti-6Al-4V alloys made by the SLM method: Banu et al [16] investigated the chemical properties of SLM Ti alloys in a lactic acid environment and observed that the corrosion resistance rate of Ti alloys by the SLM method was lower than that of wrought alloys; Cheng et al [17] investigated Ti alloys with 0.3 wt.% Zn additions, and concluded they had better impact toughness and stable high-temperature tensile mechanical properties; Ben-Hamu et al [18] investigated the corrosion resistance of Ti-6Al-4V in 0.9 M NaCl solution under EBM and SLM fabrication methods, and the results show that the corrosion resistance of SLM method Ti-6Al-4V alloys is slightly superior to that of the EBM method Ti-6Al-4V in both the XY and XZ planes.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research has been conducted on cast Ti-6Al-4V. Feng et al [12], Zhu et al [13], Lee et al [14], and Wen et al [15] have determined the mechanical properties of Ti-6Al-4V cast alloys and the mechanical properties of Ti-6Al-4V casting alloys in terms of the machining conditions, the addition of Ti-TiB2 nanoparticles, vacuum centrifugation, Ni sandwich method from a single point of view, and the mechanical properties of Ti-6Al-4V casting alloys and the mechanical properties of Ti-6Al-4V casting alloys from a single point of view, in addition to 4V casting alloy's mechanical properties as well as strength. In addition, some scholars have also investigated the properties of Ti-6Al-4V alloys made by the SLM method: Banu et al [16] investigated the chemical properties of SLM Ti alloys in a lactic acid environment and observed that the corrosion resistance rate of Ti alloys by the SLM method was lower than that of wrought alloys; Cheng et al [17] investigated Ti alloys with 0.3 wt.% Zn additions, and concluded they had better impact toughness and stable high-temperature tensile mechanical properties; Ben-Hamu et al [18] investigated the corrosion resistance of Ti-6Al-4V in 0.9 M NaCl solution under EBM and SLM fabrication methods, and the results show that the corrosion resistance of SLM method Ti-6Al-4V alloys is slightly superior to that of the EBM method Ti-6Al-4V in both the XY and XZ planes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the use of Ti alloys is increasing in the aerospace field. However, due to the characteristics of the aerospace field, high-temperature forming methods such as ring-rolling are applied because they are often applied to parts with complex shapes, and the high-temperature ring-rolling process used in aircraft engines is generally applied [4,5]. This ring-rolling is largely involved in the change of the microstructure according to the process variables and thus shows the difference in mechanical properties [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many high-temperature processing methods such as hot rolling, hot forging, and hot forming are applied. In particular, it is known that a ring-rolling process is generally used in the manufacture of Ti alloys for aircraft engines [9,10].…”
Section: Introductionmentioning
confidence: 99%